Full interhemispheric integration sustained by a fraction of posterior callosal fibers - Tyler Santander; Selin Bekir; Theresa Paul; Jessica M. Simonson; Valerie M. Wiemer; Henri Etel Skinner; Johanna L. Hopf; Anna Rada; Friedrich G. Woermann; Thilo Kalbhenn; Barry Giesbrecht; Christian G. Bien; et al. (Proceedings of the National Academy of Sciences, 2025)
The dynamic integration of the lateralized and specialized capacities of the two cerebral hemispheres constitutes a hallmark feature of human brain function. This interhemispheric exchange of information critically depends upon the corpus callosum. Classical anatomical descriptions of callosal organization outline a topographic gradient from front to back, such that specific transcallosal fibers support distinct aspects of integrated brain function. Here, we present a challenge to this conventional model. Using neuroimaging data obtained from a new cohort of adult corpus callosotomy patients, we leverage modern network neuroscience techniques to show that full interhemispheric integration can be achieved via a small proportion of posterior callosal fibers. Partial callosotomy patients with spared callosal fibers retained widespread patterns of interhemispheric functional connectivity and showed no signs of behavioral disconnection, even with only 1 cm of the splenium intact. Conversely, only complete callosotomy patients demonstrated sweeping disruptions of interhemispheric network architectures, aligning with disconnection syndromes long-thought to reflect diminished information propagation and communication across the brain. These findings motivate an evolving mechanistic understanding of synchronized interhemispheric neural activity for large-scale human brain function and behavior.